Interaction Design of Refreshable Braille Display to Support Learning for The Visually Impaired Kids - Anisa Ayu Muttaqina; Andhika Estiyono; Ari Dwi Krisbianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2019)
Impaired vision is a condition where someone is unable to see clearly, even when they are using glasses and in condition where there is enough amount of light. Impaired vision in Indonesia is not only become health problem, but has already become social problem. One of the social needs is education. However, people with impaired vision have differences way in how they learn, because they use braille characters in their education process. There is a device to support the braille learning which name is refreshable braille display. However, the devices are usually sold in a very expensive price. Based on the background and the above phenomenon, this research is about to do the design of low-cost refreshable braille display for educational needs.